The representations of Palestinians behavioral attributes in Hollywood movies from 2000 to 2014 - Saed Juneidi; Mohd Nizam Osman; Megat Al-Imran Yasin; Rosya Izyanie Shamshudeen; Mohd Nor Shahizan Ali (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since the period followed the September 11 in 2001 attack, and the second Palestinian uprising in 2000, Hollywood has produced many movies representing the Arab. The representation was shown in certain positions and scenes in the movie to give a certain meaning. Further, most of these previous studies have studied the personality in Hollywood movies combined with Arab characters. However, this study seeks to explore the behavioural attributes of the Palestinian character represented in Hollywood feature movies from the year 2000 to 2014 in detailed analysis. A literature analysis reviewed Arab representations in Hollywood movies. The quantitative approach is adopted as well as the data has been collected by employing the quantitative content analysis through using a coding sheet. The sample selection of this study is total population sampling. The unit analysis is 71 scenes that include and involve Palestinian character(s) within the five Hollywood feature movies. This study has approved that after the second Palestinian uprising in 2000 and September 2001 attack, the Palestinian behavioural attributes began to change. Thus, the behavioural attributes of The Palestinian character have represented in more complexity than the previous representation. Additionally, this study has observed that, after the September attack, Hollywood has modified the Palestinian behavioural representation.